2022
DOI: 10.1186/s12936-021-04020-6
|View full text |Cite
|
Sign up to set email alerts
|

Naturally acquired antibody response to a Plasmodium falciparum chimeric vaccine candidate GMZ2.6c and its components (MSP-3, GLURP, and Pfs48/45) in individuals living in Brazilian malaria-endemic areas

Abstract: Background The GMZ2.6c malaria vaccine candidate is a multi-stage Plasmodium falciparum chimeric protein which contains a fragment of the sexual-stage Pfs48/45-6C protein genetically fused to GMZ2, a fusion protein of GLURP and MSP-3, that has been shown to be well tolerated, safe and immunogenic in clinical trials performed in a malaria-endemic area of Africa. However, there is no data available on the antigenicity or immunogenicity of GMZ2.6c in humans. Considering that circulating parasites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…A number of 6-cysteine multi-antigen vaccine candidates are under investigation, including Pfs48/45-GLURP ( Theisen et al., 2014 ; Roeffen et al., 2015 ; Singh et al., 2015 ; Singh et al., 2017a ; Singh et al., 2017b ; Singh et al., 2021a ), Pfs48/45-GLURP-MSP3 ( Baldwin et al., 2016 ; Mistarz et al., 2017 ), Pfs230-Pfs48/45 ( Singh et al., 2019 ; Singh et al., 2020 ; Singh et al., 2021b ) and Pfs230-Pfs25 ( Menon et al., 2017 ; Healy et al., 2021 ). A recent study found a higher prevalence of naturally infected individuals with antibodies against a Pfs48/45-GLURP-MSP3-based vaccine than against the individual proteins, suggesting the combination of antigens has an additive effect on immune response ( Baptista et al., 2022 ). Moreover, animal immunization with the Pfs230-Pfs48/45 chimera elicited transmission-blocking antibody responses three-fold higher than the single antigens alone ( Singh et al., 2019 ), suggesting further investigation of 6-cysteine antigen combinations is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A number of 6-cysteine multi-antigen vaccine candidates are under investigation, including Pfs48/45-GLURP ( Theisen et al., 2014 ; Roeffen et al., 2015 ; Singh et al., 2015 ; Singh et al., 2017a ; Singh et al., 2017b ; Singh et al., 2021a ), Pfs48/45-GLURP-MSP3 ( Baldwin et al., 2016 ; Mistarz et al., 2017 ), Pfs230-Pfs48/45 ( Singh et al., 2019 ; Singh et al., 2020 ; Singh et al., 2021b ) and Pfs230-Pfs25 ( Menon et al., 2017 ; Healy et al., 2021 ). A recent study found a higher prevalence of naturally infected individuals with antibodies against a Pfs48/45-GLURP-MSP3-based vaccine than against the individual proteins, suggesting the combination of antigens has an additive effect on immune response ( Baptista et al., 2022 ). Moreover, animal immunization with the Pfs230-Pfs48/45 chimera elicited transmission-blocking antibody responses three-fold higher than the single antigens alone ( Singh et al., 2019 ), suggesting further investigation of 6-cysteine antigen combinations is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples from 303 malaria-exposed individuals identified as responders to GLURP 27−500 ( n = 258), MSP-3 155–249 ( n = 170), and/or Pf s48/45 291–428 ( n = 108) recombinants ( Table S1 ), as previously described [ 20 ], were used to investigate specific naturally acquired antibody response to GLURP, MSP-3, and Pf s48/45 epitopes. In addition, serum samples from 5 individuals of the laboratory staff (Rio de Janeiro, Brazil) who had neither history of malaria nor contact with malaria transmission areas were included in our study (Rio de Janeiro controls).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that GMZ2.6c protein was widely recognized by naturally acquired antibodies from individuals of Brazilian endemic areas and that its components (MSP-3, GLURP, and Pf s48/45) are immunogenic in natural infection by P. falciparum. Moreover, anti-GMZ2.6c antibodies seem to increase with exposure to malaria infection and may contribute to parasite immunity [ 20 ]. Considering that antibodies recognize several antigenic determinants of the protein, identifying the contribution of different immunodominant B-cell epitopes of antimalarial vaccine candidates that induce specific immune responses may be an important tool for understanding protective immunity.…”
Section: Introductionmentioning
confidence: 99%
“…GMZ2.6c vaccine efficacy can be enhanced by using TLR4 agonists which have been reported to induce parasite-specific antibodies and T-cell-mediated immunity in mice models ( 170 ). Recently, one study reported that the GMZ2.6c vaccine is recognized by naturally acquired antibodies in individuals living in malaria-endemic regions of Brazil with different levels of transmission ( 171 ). Another chimeric multistage TBV, ProC6C was prepared by combining Pf s230- Pf s48/45 fusion protein with the Pf CSP linker sequence.…”
Section: Vaccine Candidates Against Plasmodiummentioning
confidence: 99%